2007
DOI: 10.1073/pnas.0700732104
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in the gene expression pattern of primary monocytes after adhesion to endothelial cells

Abstract: Monocytes originate from precursors made in the bone and remain in the circulation for nearly 24 h. Much effort has been done to identify the molecules regulating transendothelial migration of monocytes during inflammatory conditions. In contrast, considerably less is known about the process of constitutive monocyte emigration although nearly 340 million monocytes leave the circulation each day in healthy individuals. Previous studies indicated that chemokines were up-regulated in monocytes cocultured with end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 46 publications
2
38
0
1
Order By: Relevance
“…Although the expression of caveolin-1 in immune cells has long been debated [14], a body of evidence indicates that macrophages actually express caveolin-1 in pathological conditions [15]. In addition, it is reported that the expression of caveolin-1 gene is up-regulated in monocytes after activation by adhesion to endothelial cells [16]. The present study provides additional evidence indicating that caveolin-1 plays roles in tissue injuries through cells of the mononuclear phagocytic system.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Although the expression of caveolin-1 in immune cells has long been debated [14], a body of evidence indicates that macrophages actually express caveolin-1 in pathological conditions [15]. In addition, it is reported that the expression of caveolin-1 gene is up-regulated in monocytes after activation by adhesion to endothelial cells [16]. The present study provides additional evidence indicating that caveolin-1 plays roles in tissue injuries through cells of the mononuclear phagocytic system.…”
Section: Discussionsupporting
confidence: 54%
“…Total RNA was extracted from fresh tissues of right cerebral cortex and hippocampus using the acid guanidium thiocyanate-phenol method. Five mg of each total RNA was reversely transcribed for the synthesis of the first strand cDNA using 500 pmol of oligodT [12][13][14][15][16][17][18] (Amersham Biosciences Corp., Arlington Heights, IL) and 200 units of SuperScript II (Gibco BRL, Gaithersburg, MD).…”
Section: Rt-pcrmentioning
confidence: 99%
“…These cross-linked receptors display enhanced activity, which is associated with increased adhesion of monocytes to the endothelium and increased symptoms of atherosclerosis in ApoE-deficient mice [40]. Attachment of monocytes to endothelial cells induces an upregulation of type 2 Tgase in monocytes, and is considered to participate in the process of cell adhesion and transmigration [41]. When monocytes are placed into culture and mature into macrophages, a shift from factor XIII expression to type 2 Tgase is noted [42].…”
Section: Atherosclerosismentioning
confidence: 99%
“…To test this, and given the difficulties in transfecting and working with LECs in vitro, we used HUVECs as a model of inflammatory leukocyte binding to endothelial cells. 40 In this model, HUVECs are treated with TNF to induce inflammatory CC-chemokines (including CCL2), selectins, and intergrins. These are presented on the HUVEC surface allowing attachment of THP-1 or other inflammatory chemokine receptor-bearing cells.…”
mentioning
confidence: 99%